2014
DOI: 10.1063/1.4870232
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric relaxations and alternating current conductivity in manganese substituted cobalt ferrite

Abstract: Manganese (Mn) substituted cobalt ferrites (CoFe 2-x Mn x O 4 , referred to CFMO) have been synthesized by the solid state reaction method and their dielectric properties and ac conductivity have been evaluated as a function of applied frequency and temperature. X-ray diffraction measurements indicate that CFMO crystallize in the inverse cubic spinel phase with a lattice constant $8.38 Å . Frequency dependent dielectric measurements at room temperature obey the modified Debye model with relaxation time of 10 À… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
69
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(76 citation statements)
references
References 62 publications
(83 reference statements)
6
69
1
Order By: Relevance
“…Similar behavior was observed by Kolekar et al where doping of Mn in ferrite material gives rise to a temperature-dependent increment in the dielectric constant. 49 In the present case, the slower increase of dielectric constant at lower temperature can be explained by considering the mobility of the charge carriers. In fact, as the mobility of the charge carriers at lower temperature is low (due to lack of enough thermal energy), their rate of hopping is less.…”
Section: Dielectric Constant and Dielectric Loss Studiesmentioning
confidence: 60%
“…Similar behavior was observed by Kolekar et al where doping of Mn in ferrite material gives rise to a temperature-dependent increment in the dielectric constant. 49 In the present case, the slower increase of dielectric constant at lower temperature can be explained by considering the mobility of the charge carriers. In fact, as the mobility of the charge carriers at lower temperature is low (due to lack of enough thermal energy), their rate of hopping is less.…”
Section: Dielectric Constant and Dielectric Loss Studiesmentioning
confidence: 60%
“…At low frequencies, the conductivity is found to be nearly frequency independent, which is considered as a dc plateau. 12,26,27 This is a typical behavior of ionic materials for the frequency region of constant conductivity (r dc ) extends to higher frequencies with increasing temperature. 27 The transition from the frequencyindependent to the frequency-dependent region signals the onset of conductivity relaxation phenomena.…”
Section: Ac Conductivity Analysismentioning
confidence: 95%
“…The specimen is more resistive at room temperature. It is observed that arc of semicircle decreases as temperature increases which indicates the bulk resistance decrease at high temperature [29]. It gives the clue that resistance of grains is the main barrier for movement of ions.…”
mentioning
confidence: 92%
“…This observation is consistent with dielectric results. However, in present study, spectrum contains a single semicircle which represents the contribution of grain interior (bulk) [29]. An equivalent circuit consisting of resistance of grains (R g ), resistance of grain boundary (R gb ), capacitance of grains (C g ) and capacitance of grain boundary (C gb ) were suggested and values of R g , R gb , C g and C gb , were determined as listed in Table II.…”
mentioning
confidence: 99%